Multilayered electronic component
The core-shell structured dielectric crystal grains with a polygonal core enhance dielectric capacity and DC-Bias characteristics, addressing the challenges of miniaturization and high capacity in multilayer ceramic capacitors by optimizing the core-shell ratio and reducing grain boundary defects.
Patent Information
- Application Number
- JP2024074436
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-14
- Filing Date
- 2024-05-01
- Publication Date
- 2025-01-24
AI Technical Summary
Existing multilayer ceramic capacitors face challenges in achieving miniaturization and high capacity while maintaining reliable dielectric capacitance and DC-Bias characteristics due to thin dielectric layers leading to increased electrical conductivity and decreased insulation resistance.
The use of dielectric crystal grains with a core-shell structure, where the core portion has a polygonal shape and a hexahedral form, with a volume fraction of 30% or more, and an average length of 80-200 nm, enhances the dielectric capacity and DC-Bias characteristics by optimizing the core-shell ratio and reducing grain boundary defects.
This structure improves the dielectric capacity, room temperature dielectric constant, and DC-Bias characteristics, ensuring higher reliability and insulation resistance, even under applied electric fields.
Smart Images

Figure 2025013164000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a multilayer electronic component. [Background technology]
[0002] Multi-Layered Ceramic Capacitor (MLCC), a type of multi-layered electronic component, is a chip-type capacitor that is mounted on the printed circuit boards of various electronic products such as visual devices such as liquid crystal displays (LCDs) and plasma display panels (PDPs), computers, smartphones, and mobile phones to charge and discharge electricity.
[0003] Such multilayer ceramic capacitors have the advantages of being small yet high capacitance and easy to mount, and can be used as components of various electronic devices. As various electronic devices such as computers and mobile devices become smaller and have higher output, there is an increasing demand for multilayer ceramic capacitors to be smaller and have higher capacitance.
[0004] Meanwhile, in order to achieve miniaturization and high capacity of multilayer electronic components, a thin dielectric layer can be applied, but as the dielectric layer becomes thinner, the number of dielectric grain boundaries decreases, which may cause the insulation resistance of the multilayer electronic components to deteriorate, or the electrical conductivity to increase, resulting in a decrease in reliability, and the dielectric capacitance characteristics and DC-Bias characteristics may also decrease. Therefore, research is being actively conducted to increase the dielectric capacitance by improving the crystallinity of the core part, which corresponds to the inside of the dielectric material, and to manufacture the shell part, which corresponds to the outside, to have a high concentration of additive distribution so that it has a relatively high insulation resistance when an electric field is applied, thereby increasing reliability. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Korean Patent Publication No. 10-2017-0127647 [Patent Document 2] Korean Patent Publication No. 10-2018-0073359 Summary of the Invention [Problem to be solved by the invention]
[0006] One of the various problems that the present invention aims to solve is to achieve miniaturization and high capacity of a multilayer electronic component.
[0007] One of the various problems that the present invention aims to solve is to increase the fraction of the core portion and thereby improve the dielectric capacitance characteristics.
[0008] One of the various problems that the present invention aims to solve is to improve the DC-Bias characteristics of a multilayer electronic component.
[0009] However, the various problems to be solved by the present invention are not limited to the above-mentioned contents, and can be more easily understood in the course of describing specific embodiments of the present invention. [Means for solving the problem]
[0010] A multilayer electronic component according to one embodiment of the present invention includes a main body including a dielectric layer and an internal electrode, and an external electrode disposed on the main body, wherein the dielectric layer includes a plurality of dielectric crystal grains, at least one of the plurality of dielectric crystal grains has a core-shell structure including a core portion and a shell portion surrounding at least a portion of the core portion, a cross section of the core portion includes a polygonal shape, an average length of the plurality of dielectric crystal grains is 80 nm or more and 200 nm or less, and a length of the core portion relative to a diameter of the dielectric crystal grain may be 70% or more.
[0011] A multilayer electronic component according to another embodiment of the present invention includes a main body including a dielectric layer and an internal electrode, and an external electrode disposed on the main body, wherein the dielectric layer includes a plurality of dielectric crystal grains, at least one of the plurality of dielectric crystal grains has a core-shell structure including a core portion and a shell portion surrounding at least a portion of the core portion, the core portion has a hexahedral shape, the average length of the plurality of dielectric crystal grains is 80 nm or more and 200 nm or less, and the volume of the core portion relative to the volume of the dielectric crystal grains may be 30% or more. Effect of the Invention
[0012] One of the various effects of the present invention is to achieve miniaturization and high capacity of a multilayer electronic component.
[0013] One of the various effects of the present invention is to improve the room temperature dielectric constant characteristics of a multilayer electronic component.
[0014] One of the various effects of the present invention is to improve the DC-Bias characteristics of a multilayer electronic component.
[0015] However, the various yet significant advantages and effects of the present invention are not limited to the above, and can be more easily understood in the course of describing specific embodiments of the present invention. [Brief description of the drawings]
[0016] [Figure 1] 1 is a schematic perspective view of a multilayer electronic component according to an embodiment of the present invention; [Diagram 2] 2 is a schematic exploded perspective view showing a laminated structure of internal electrodes; FIG. [Diagram 3] 2 is a schematic cross-sectional view taken along line II' of FIG. 1. [Figure 4] 2 is a schematic cross-sectional view taken along line II-II' in FIG. 1. [Diagram 5] 4 is a schematic diagram showing an enlarged view of region P in FIG. 3. [Figure 6]1 is a schematic diagram of a dielectric grain according to an embodiment of the present invention; [Figure 7] 1 is a schematic representation of a dielectric particle; [Figure 8] 1A is an image of a dielectric crystal grain according to an embodiment of the present invention taken with a transmission electron microscope (TEM), 1B is an image of a dielectric crystal grain according to an embodiment of the present invention taken with a transmission electron microscope (TEM), 1B is an image of a dielectric crystal grain according to an embodiment of the present invention taken with a transmission electron microscope (TEM), and 1D is an image of a dielectric crystal grain according to an embodiment of the present invention taken with an EDS analysis. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Hereinafter, the embodiments of the present invention will be described with reference to specific embodiments and the accompanying drawings. However, the embodiments of the present invention can be modified into several other forms, and the scope of the present invention is not limited to the embodiments described below. Furthermore, the embodiments of the present invention are provided to more completely explain the present invention to those skilled in the art. Therefore, the shapes and sizes of elements in the drawings may be enlarged or reduced (or highlighted or simplified) for clearer explanation, and elements indicated by the same reference numerals in the drawings are the same elements.
[0018] In addition, in the drawings, parts that are not relevant to the description are omitted in order to clearly explain the present invention, and the size and thickness of each component shown in the drawings are arbitrarily shown for convenience of explanation, so the present invention is not necessarily limited by the drawings. Furthermore, components having the same function within the same concept may be described using the same reference numerals. Furthermore, throughout the specification, when a part "includes" a certain component, it does not mean that the part excludes other components, but that the part may further include other components, unless otherwise specified to the contrary.
[0019] In the drawings, the first direction can be defined as the stacking direction or thickness (T) direction, the second direction can be defined as the length (L) direction, and the third direction can be defined as the width (W) direction.
[0020] Multilayer Electronic Components FIG. 1 is a schematic perspective view of a multilayer electronic component according to one embodiment of the present invention, FIG. 2 is a schematic perspective view showing a separated layered structure of an internal electrode, FIG. 3 is a schematic cross-sectional view taken along line I-I' in FIG. 1, FIG. 4 is a schematic cross-sectional view taken along line II-II' in FIG. 1, FIG. 5 is a schematic enlarged view of region P in FIG. 3, FIG. 6 is a schematic view of dielectric crystal grains according to one embodiment of the present invention, and FIG. 7 is a schematic view of a dielectric particle.
[0021] Hereinafter, a multilayer electronic component according to an embodiment of the present invention will be described in detail with reference to Figures 1 to 7. Although a multilayer ceramic capacitor will be described as an example of a multilayer electronic component, the present invention can also be applied to various electronic products that use dielectrics, such as inductors, piezoelectric elements, varistors, thermistors, etc.
[0022] A multilayer electronic component 100 according to one embodiment of the present invention includes a body 110 including a dielectric layer 111 and internal electrodes 121, 122, and external electrodes 131, 132 arranged on the body 110, the dielectric layer 111 including a plurality of dielectric crystal grains, at least one of the plurality of dielectric crystal grains having a core-shell structure 10 including a core portion 11 and a shell portion 12 surrounding at least a portion of the core portion 11, the cross section of the core portion 11 having a polygonal shape, the average length of the plurality of dielectric crystal grains being 80 nm or more and 200 nm or less, and the length of the core portion 11 relative to the diameter of the dielectric crystal grain 10 may be 705% or less.
[0023] The body 110 has dielectric layers 111 and internal electrodes 121 and 122 laminated alternately.
[0024] More specifically, the main body 110 may include a capacitance forming portion Ac that is disposed inside the main body 110 and includes first internal electrodes 121 and second internal electrodes 122 that are alternately arranged facing each other across the dielectric layer 111 to form a capacitance.
[0025] Although there is no particular limitation on the specific shape of the body 110, the body 110 may be hexahedral or a similar shape as shown in the figure. Due to shrinkage of the ceramic powder contained in the body 110 during the firing process, the body 110 may not be a hexahedral shape with perfectly straight lines, but may be substantially hexahedral.
[0026] The main body 110 may have a first surface 1 and a second surface 2 facing each other in a first direction, a third surface 3 and a fourth surface 4 connected to the first surface 1 and the second surface 2 and facing each other in the second direction, and a fifth surface 5 and a sixth surface 6 connected to the first surface 1, the second surface 2, the third surface 3 and the fourth surface 4 and facing each other in the third direction.
[0027] The plurality of dielectric layers 111 forming the body 110 are in a fired state, and the boundaries between adjacent dielectric layers 111 can be integrated to such an extent that they are difficult to see without the use of a scanning electron microscope (SEM).
[0028] The raw material for forming the dielectric layer 111 is not limited as long as a sufficient capacitance can be obtained. In general, a perovskite (ABO3)-based material can be used, such as a barium titanate-based material, a lead complex perovskite-based material, or a strontium titanate-based material. The barium titanate-based material can include a BaTiO3-based ceramic powder, and examples of the ceramic powder include BaTiO3, BaTiO3 partially solid-dissolved with Ca (calcium), Zr (zirconium), etc. 1-x Ca x )TiO3(0 <x<1)、Ba(Ti 1-y Ca y )O3(0 <y<1)、(Ba 1-x Ca x )(Ti 1-yZr y )O3 (0 < x < 1, 0 < y < 1) or Ba(Ti 1-y Zr y )O3 (0 < y < 1), etc. can be mentioned.
[0029] Also, as the raw material for forming the dielectric layer 111, various ceramic additives, organic solvents, binders, dispersants, etc. can be added to powders such as barium titanate (BaTiO3) according to the purpose of the present invention.
[0030] The thickness of the dielectric layer 111 does not need to be particularly limited.
[0031] However, in order to more easily achieve miniaturization and high capacitance of the multilayer electronic component, the thickness of the dielectric layer 111 can be 0.6 μm or less, preferably 0.45 μm or less, and more preferably 0.4 μm or less.
[0032] Here, the thickness td of the dielectric layer 111 can mean the thickness td of one dielectric layer 111 disposed between the first internal electrode 121 and the second internal electrode 122, but preferably means the thickness td of all the dielectric layers.
[0033] On the other hand, the thickness td of the dielectric layer 111 can mean the size of the dielectric layer 111 in the first direction. Also, the thickness td of the dielectric layer 111 can mean the average thickness td of the dielectric layer 111 and can mean the average size of the dielectric layer 111 in the first direction.
[0034] The average size in the first direction of the dielectric layer 111 may be measured by scanning an image of a cross-section in the first and second directions of the body 110 using a scanning electron microscope (SEM) with a magnification of 10,000. More specifically, the average size in the first direction of one dielectric layer 111 may mean an average value calculated by measuring the size in the first direction of one dielectric layer 111 at 30 equally spaced points in the second direction in the scanned image. The 30 equally spaced points may be designated as the capacitance forming portion Ac. Furthermore, if such an average value measurement is extended to 10 dielectric layers 111 to measure the average value, the average size in the first direction of the dielectric layer 111 may be further generalized.
[0035] Meanwhile, in order to achieve miniaturization and high capacity of multilayer electronic components, a thin dielectric layer can be applied, but as the dielectric layer becomes thinner, the number of dielectric grain boundaries decreases, which may cause the insulation resistance value of the multilayer electronic component to deteriorate, or the electrical conductivity to increase, resulting in a decrease in reliability, and the dielectric capacitance characteristics and DC-Bias characteristics may also decrease. Therefore, the crystallinity of the core portion, which corresponds to the inside of the dielectric material, is improved to increase the dielectric capacitance, and the shell portion, which corresponds to the outside, is manufactured to have a high concentration of additive distribution, which allows the shell portion to have a relatively high insulation resistance value when an electric field is applied, thereby increasing reliability.
[0036] The dielectric material contained in the dielectric layer 111, for example, a barium titanate (BaTiO3)-based dielectric, generally has a tetragonal crystal lattice structure at room temperature, but a region where some elements such as additives are substituted, for example, a shell, can be transformed into a cubic crystal lattice structure. By transforming the lattice structure of the shell in the dielectric material, it can be switched to a phase in which a dipole moment due to a tetragonal structure and a cubic structure exists, thereby improving the dielectric characteristics.
[0037] As a result, the dielectric layer 111 of one embodiment according to the present invention includes a plurality of dielectric crystal grains, and at least one of the plurality of dielectric crystal grains can have a core-shell structure 10 including a core portion 11 and a shell portion 12 surrounding at least a portion of the core portion 11. That is, the dielectric layer 111 can include dielectric crystal grains having the core-shell structure 10 and dielectric crystal grains not having a core-shell structure.
[0038] It is known that the effective capacitance of a dielectric is improved when the size of the region having a tetragonal crystal lattice structure is larger than the size of the region having a cubic crystal lattice structure in the dielectric crystal grain. In other words, the dielectric constant can be improved as the ratio of (size of tetragonal crystal lattice structure / cubic crystal lattice structure) is larger in a dielectric microstructure of the same size of dielectric crystal grain.
[0039] In the shell region where some elements such as additives are replaced, domain walls may be generated due to defects in the lattice caused by ion defects such as oxygen vacancies and defect dipoles in units of lattice size, and such defective lattices may cause irreversible domain wall motion when an electric field is applied, which may cause a decrease in effective capacity that can be realized when a voltage is applied. That is, as the shell region is doped with additives, insulation resistance characteristics are improved and reliability is increased, but effective capacity may be decreased when voltage is applied.
[0040] Therefore, when the core size increases relative to the dielectric crystal grain size, the effective capacitance can be improved when a DC-Bias voltage is applied.
[0041] In the present invention, in order to maximize the room temperature dielectric constant, the dielectric capacitance characteristics, or the effective capacitance when a voltage is applied, the shape of the core in the dielectric crystal grains is controlled to minimize the grain growth rate, thereby ensuring the dielectric capacitance, improving the reduction rate of the dielectric constant, and improving the DC-Bias characteristics.
[0042] The dielectric crystal grains included in the dielectric layer may have a three-dimensional shape, but since the conventional core portion has a spherical shape (with a circular cross section), the core portion may relatively decrease due to grain growth, and as sintering proceeds at a low temperature due to the relatively high surface energy, the dispersibility of additives may decrease, or pores may be located at the triple points of the dielectric crystal grain boundaries, resulting in reduced reliability.
[0043] Meanwhile, the core portion 11 according to an embodiment of the present invention may have a hexahedral shape.
[0044] Since the core portion 11 of the dielectric crystal grain 10 has a hexahedral shape, the ratio of the core portion 11 within the dielectric crystal grain 10 can be increased, the size ratio with the shell portion 12 can be optimized, and the generation of pores due to gap-free sintering during the firing process can be suppressed, thereby improving the dielectric capacitance and reliability.
[0045] This may be the result of manufacturing the dielectric particles in a hexahedral shape before sintering, doping an additive, and sintering the particles. More specifically, referring to FIG. 7, the core portion 11' of the dielectric particle 10' before sintering may have a hexahedral shape, and the shell portion 12' of the dielectric particle 10' doped with an additive may also have a hexahedral shape, but is not particularly limited thereto.
[0046] In the present invention, the dielectric particles may refer to the dielectric material before sintering, and the dielectric grains may refer to the dielectric material after sintering. In addition, a dielectric grain boundary may be disposed between the dielectric grains, and a triple point may be disposed at a point where three or more dielectric grains (or dielectric grain boundaries) meet. The definitions of terms described in the present invention may follow the definitions of terms generally used in the technical field of the present invention, unless otherwise specified.
[0047] In general, the size of the core observed in the dielectric crystal grain after sintering tends to be determined by the size of the dielectric particle before sintering, and since the size of the core can be controlled so as to have almost no effect during the stage of sintering or grain growth of the dielectric particle, the size and grain growth rate of the dielectric particle before sintering can be predicted from the core size of the dielectric crystal grain after sintering.
[0048] The fine-structured dielectric crystal grains can be easily observed by observing the dielectric layer 111 located at the center of the capacitance forming portion Ac based on the cross-sections in the first and second directions of the body 110 through a scanning electron microscope (SEM) or a transmission electron microscope (TEM), and at this time, the cross-section of the core portion can be exposed.
[0049] Therefore, in the following, the shape of the core portion 11 according to one embodiment of the present invention will be described based on the cross section.
[0050] According to an embodiment of the present invention, the cross-section of the core portion 11 may include various polygonal shapes, in other words, the cross-sections of the core portions 11 of the multiple dielectric crystal grains may have different polygonal shapes.
[0051] When the cross section of the core portion 11 includes a polygonal shape, the core portion 11 can have a high fraction inside the dielectric crystal grain 10 having the core-shell structure, thereby improving the dielectric capacitance and DC-Bias characteristics.
[0052] In the present invention, a polygon does not only mean a polygon consisting of straight lines, but can also include a polygon with rounded corners (no vertices), and can mean a substantial polygonal shape.
[0053] Here, the polygon may include one or more of triangles including equilateral triangles and isosceles triangles, quadrilaterals including squares, rectangles, rhombus, trapezoids, equilateral trapezoids and parallelograms, pentagons and hexagons, and the sum of the interior angles of the polygon may be substantially one or more of 180°, 360°, 540° and 720° depending on the definition of the polygon, but is not particularly limited thereto. Here, the meaning that the sum of the interior angles is substantially one or more of 180°, 360°, 540° and 720° may mean that an error of about ±5° is included.
[0054] In particular, a polygon in the present invention may mean a polygon obtained at a cross-section of a cube.
[0055] At least a part of the cross-sectional shape of the core portion 11 may be substantially parallel to the dielectric grain boundaries, which can improve the dielectric properties compared to a circular core portion cross section.
[0056] Here, the meaning of at least a part of the cross-sectional shape of core portion 11 being substantially parallel to the dielectric crystal grain boundary can mean that one boundary line between core portion 11 and shell portion 12 is substantially parallel to the dielectric crystal grain boundary, and the meaning of substantially parallel does not mean absolutely parallel, but can mean that 50% or more of one side (virtual straight line) of core portion 11, which is one boundary line between core portion 11 and shell portion 12 described below, is substantially parallel to the dielectric crystal grain boundary.
[0057] Referring to an embodiment of the present invention, FIG. 8(a) is an image of a dielectric crystal grain of an embodiment of the present invention photographed through a transmission electron microscope (TEM), FIG. 8(b) is an image of a dysprosium (Dy) element mapping obtained by performing an energy dispersive X-ray spectroscopy (EDS) analysis on FIG. 8(a) and FIG. 8(c) is an image of a dielectric crystal grain of an embodiment of the present invention photographed through a transmission electron microscope (TEM), and FIG. 8(d) is an image of a dysprosium (Dy) element mapping obtained by performing an EDS analysis on FIG. 8(c).
[0058] As can be seen from Figures 8(b) and 8(d), at least one of the multiple dielectric crystal grains contained within an image measuring 1.0 μm wide x 0.6 μm long has a core-shell structure and is composed of multiple polygonal core portions of different shapes.
[0059] The interior angles of the polygon can be determined by measuring the angle (∠a°) between straight lines L1 and L2 extending from different sides, based on a cross-section of the core portion 11 photographed with a scanning electron microscope (SEM) or a transmission electron microscope (TEM).
[0060] Here, the sides of the polygon may refer to straight lines having a length of 50% or more based on the minimum length passing through the center of the core portion 11 of the dielectric crystal grain, and the polygon may refer to a shape in which the cross section of the core portion 11 includes three or more sides, and preferably a shape in which the cross section includes three or more and six or less sides, but is not particularly limited thereto.
[0061] On the other hand, the volume fraction of the core portion 11 with respect to the volume of the dielectric crystal grains 10 is preferably 30% or more.
[0062] By making the volume fraction of the core portion 11 relative to the volume of the dielectric crystal grains 10 of the core-shell structure 30% or more, the target dielectric capacitance and room temperature dielectric constant can be achieved, and the DC-Bias characteristics can be improved.
[0063] If the volume fraction of the core portion 11 is 30% or less, the dielectric characteristics of the core portion 11 may be insufficient, decreasing the magnitude of the dielectric constant, and there is a risk of deteriorating the DC-Bias characteristics or high-temperature reliability.
[0064] The length of the core portion 11 relative to the length of the dielectric crystal grain 10 may be 70% or more.
[0065] Here, the length of the core portion 11 may refer to the maximum length D having the longest length among straight lines passing through the center of the core portion 11. In addition, the length of the dielectric crystal grain 10 may refer to including a straight line extending from a straight line passing through the maximum length of the core portion 11, and may refer to the combined length of the core portion 11 and the shell portion 12.
[0066] By making the length of the core portion 11 to be 70% or more of the length of the dielectric crystal grains 10 of the core-shell structure, the target dielectric capacitance and room temperature dielectric constant can be achieved, and the DC-Bias characteristics can be improved.
[0067] If the length of the core portion 11 relative to the diameter of the dielectric crystal grain 10 of the core-shell structure is less than 70%, it may be difficult to form a sufficient dielectric capacitance, and the DC-Bias characteristics may deteriorate.
[0068] The length of the core portion 11 relative to the length of the dielectric crystal grain 10 can be 95% or less, or 90% or less, but is not particularly limited to this. This is because it is expected that a problem of reduced reliability may occur if the area of the shell portion 12 is insufficient, and it is preferable to form the shell portion 12 to such an extent that reduced reliability does not occur, and therefore this is an example of the upper limit value.
[0069] The shell portion 12 may contain a rare earth element, and the rare earth element concentration may be higher than that of the core portion 11 .
[0070] The rare earth elements can include one or more of yttrium (Y), dysprosium (Dy), holmium (Ho), erbium (Er), gadolinium (Gd), cerium (Ce), neodymium (Nd), samarium (Sm), terbium (Tb), thulium (Tm), lanthanum (La), and ytterbium (Yb).
[0071] Meanwhile, the criteria for distinguishing the core portion 11 and the shell portion 22 can be carried out through a scanning electron microscope-energy dispersive spectroscopy (SEM-EDS: Scanning Electron Microscopy-Energy Dispersive X-ray Spectroscopy) or a transmission electron microscope-energy dispersive spectroscopy (TEM-EDS: Transmission Electron Microscopy-Energy Dispersive X-ray Spectroscopy) analysis, and the content of rare earth elements contained in the dielectric crystal grains of the core-shell structure can be measured to distinguish them.
[0072] For example, in the case of dysprosium (Dy), a type of rare earth element, it is difficult for Dy to diffuse into the core, so the region where Dy does not diffuse during EDS analysis of the dielectric crystal grains can be defined as the core, and the region that covers or surrounds the core can be defined as the shell. In other words, the region from the outside of the core, where the concentration of the rare earth element is measured to be relatively high, to the dielectric crystal grains can be defined as the shell.
[0073] Alternatively, when a line profile is used to analyze one dielectric crystal grain having a core-shell structure, the region with a low Dy content can be defined as the core portion, and the region with a high Dy content can be defined as the shell portion, based on the point where the Dy content changes abruptly.
[0074] The dielectric crystal grains according to an embodiment of the present invention may have an average length of 80 nm or more and 200 nm or less.
[0075] By making the average length of the dielectric crystal grains to be 80 nm or more and 200 nm or less, even a dielectric layer with an average thickness of 0.45 μm or less can have excellent dielectric constant or dielectric capacitance.
[0076] If the average length of the dielectric crystal grains is less than 80 nm, sufficient dielectric capacitance may not be ensured or the temperature coefficient of capacitance (TCC) may decrease, and if the average length of the dielectric crystal grains exceeds 200 nm, the insulation resistance characteristics may decrease.
[0077] In one embodiment of the present invention, when the average thickness of the dielectric layer td is 0.45 μm or less, the average length of the dielectric crystal grains is 80 nm or more and 200 nm or less, and the cross section of the core portion 11 of the dielectric crystal grains includes a polygon, the dielectric characteristics or DC-Bias characteristics can be further improved.
[0078] Here, the average length of the dielectric crystal grains may refer to an average value obtained by measuring the maximum diameters of the dielectric crystal grains observed in an image of an arbitrary 10 μm×10 μm region in the dielectric layer of the capacitance forming portion Ac using a scanning electron microscope (SEM) or a transmission electron microscope (TEM). In this case, the average length may be calculated by including not only the dielectric crystal grains 10 having the core-shell structure but also the dielectric crystal grains not having the core-shell structure.
[0079] The internal electrodes 121 and 122 may be laminated alternately with the dielectric layers 111 .
[0080] The internal electrodes 121, 122 may include a first internal electrode 121 and a second internal electrode 122, and the first internal electrode 121 and the second internal electrode 122 are alternately arranged to face each other across the dielectric layer 111 that constitutes the main body 110, and may be exposed to the third surface 3 and the fourth surface 4 of the main body 110, respectively.
[0081] More specifically, the first internal electrode 121 may be spaced apart from the fourth surface 4 and exposed through the third surface 3, and the second internal electrode 122 may be spaced apart from the third surface 3 and exposed through the fourth surface 4. A first external electrode 131 may be disposed on the third surface 3 of the body 110 and connected to the first internal electrode 121, and a second external electrode 132 may be disposed on the fourth surface 4 of the body 110 and connected to the second internal electrode 122.
[0082] That is, the first internal electrode 121 may be connected to the first external electrode 131 without being connected to the second external electrode 132, and the second internal electrode 122 may be connected to the second external electrode 132 without being connected to the first external electrode 131. In this case, the first internal electrode 121 and the second internal electrode 122 may be electrically isolated from each other by the dielectric layer 111 disposed therebetween.
[0083] Meanwhile, the body 110 may be formed by alternately stacking ceramic green sheets on which the first internal electrodes 121 are printed and ceramic green sheets on which the second internal electrodes 122 are printed, and then firing the stacked ceramic green sheets.
[0084] There are no particular limitations on the material forming the internal electrodes 121 and 122, and any material having excellent electrical conductivity can be used. For example, the internal electrodes 121 and 122 can include one or more of nickel (Ni), copper (Cu), palladium (Pd), silver (Ag), gold (Au), platinum (Pt), tin (Sn), tungsten (W), titanium (Ti), and alloys thereof.
[0085] The internal electrodes 121 and 122 may be formed by printing a conductive paste for internal electrodes, which contains at least one of nickel (Ni), copper (Cu), palladium (Pd), silver (Ag), gold (Au), platinum (Pt), tin (Sn), tungsten (W), titanium (Ti), and alloys thereof, on a ceramic green sheet. The method for printing the conductive paste for internal electrodes may be a screen printing method or a gravure printing method, but the present invention is not limited thereto.
[0086] On the other hand, the thickness te of the internal electrodes 121 and 122 does not need to be particularly limited.
[0087] However, in order to more easily achieve miniaturization and high capacity of the multilayer electronic component, the thickness of the internal electrodes 121, 122 may be 0.6 μm or less, preferably 0.45 μm or less, and more preferably 0.4 μm or less.
[0088] Here, the thickness te of the internal electrodes 121, 122 may refer to the size of the internal electrodes 121, 122 in the first direction. In addition, the thickness te of the internal electrodes 121, 122 may refer to the average thickness te of the internal electrodes 121, 122, or may refer to the average size of the internal electrodes 121, 122 in the first direction.
[0089] The average size of the internal electrodes 121, 122 in the first direction may be measured by scanning an image of a cross-section of the body 110 in the first and second directions with a scanning electron microscope (SEM) at a magnification of 10,000. More specifically, the average size of one internal electrode in the first direction may be an average value calculated by measuring the size of one internal electrode in the first direction at 30 equally spaced points in the second direction in the scanned image. The 30 equally spaced points may be designated as the capacitance forming portion Ac. Furthermore, if such an average measurement is extended to 10 internal electrodes 121, 122 to measure the average, the average size of the internal electrodes 121, 122 in the first direction may be further generalized.
[0090] Meanwhile, the body 110 may include cover portions 112 and 113 disposed on both end surfaces in the first direction of the capacitance forming portion Ac.
[0091] More specifically, the cover parts 112, 113 may include an upper cover part 112 disposed at an upper part of the capacitance forming part Ac in the first direction and a lower cover part 113 disposed at a lower part of the capacitance forming part Ac in the first direction.
[0092] The upper cover part 112 and the lower cover part 113 may be formed by stacking a single dielectric layer 111 or two or more dielectric layers 111 in a first direction on the upper and lower surfaces of the capacitance forming part Ac, respectively, and may basically serve to prevent damage to the internal electrodes 121, 122 due to physical or chemical stress.
[0093] The upper cover part 112 and the lower cover part 113 do not include the internal electrodes 121, 122 and may include the same material as the dielectric layer 111. That is, the upper cover part 112 and the lower cover part 113 may include a ceramic material, for example, a barium titanate (BaTiO3)-based ceramic material.
[0094] On the other hand, the thickness tc of the covers 112 and 113 does not need to be particularly limited.
[0095] However, in order to more easily achieve miniaturization and high capacity of the multilayer electronic component, the thickness tc of the cover parts 112, 113 can be 100 μm or less, preferably 30 μm or less, and more preferably 20 μm or less for ultra-small products.
[0096] Here, the thickness tc of the cover parts 112, 113 may refer to the size of the cover parts 112, 113 in the first direction. In addition, the thickness tc of the cover parts 112, 113 may refer to the average thickness tc of the cover parts 112, 113, or may refer to the average size of the cover parts 112, 113 in the first direction.
[0097] The average size in the first direction of the covers 112 and 113 may be measured by scanning an image of a cross section in the first and second directions of the body 110 with a scanning electron microscope (SEM) at a magnification of 10,000. More specifically, the average size in the first direction may be calculated by measuring the size in the first direction at 30 points equally spaced in the second direction in an image obtained by scanning one cover.
[0098] Furthermore, the average size in the first direction of the cover portion measured by the above-mentioned method may be substantially the same as the average size in the first direction of the cover portion in the cross-sections of the main body 110 in the first and third directions.
[0099] Meanwhile, side margin parts 114 and 115 may be disposed on both end surfaces of the body 110 in the third direction.
[0100] More specifically, the side margin portions 114, 115 may include a first side margin portion 114 disposed on the fifth surface 5 of the main body 110 and a second side margin portion 115 disposed on the sixth surface 6. That is, the side margin portions 114, 115 may be disposed on both end surfaces of the main body 110 in the third direction.
[0101] As shown in the figure, the side margin portions 114, 115 may refer to the areas between both ends of the first internal electrode 121 and the second internal electrode 122 in the third direction and the boundary surface of the body 110, based on the cross-sections in the first and third directions of the body 110.
[0102] The side margins 114 and 115 essentially serve to prevent damage to the internal electrodes 121 and 122 due to physical or chemical stress.
[0103] The side margin portions 114, 115 can also be formed by forming internal electrodes 121, 122 by applying a conductive paste to the ceramic green sheet except for the areas where the side margin portions 114, 115 are to be formed, and then cutting the laminated internal electrodes 121, 122 so that they are exposed on the fifth surface 5 and the sixth surface 6 of the main body 110 in order to suppress steps caused by the internal electrodes 121, 122, and then stacking a single dielectric layer 111 or two or more dielectric layers 111 in the third direction on both end surfaces in the third direction of the capacitance forming portion Ac.
[0104] The first side margin portion 114 and the second side margin portion 115 do not include the internal electrodes 121, 122, and may include the same material as the dielectric layer 111. That is, the first side margin portion 114 and the second side margin portion 115 may include a ceramic material, for example, a barium titanate (BaTiO3)-based ceramic material.
[0105] On the other hand, the width wm of the first side margin portion 114 and the second side margin portion 115 does not need to be particularly limited.
[0106] However, in order to more easily achieve miniaturization and high capacity of the laminated electronic component 100, the width wm of the first side margin portion 114 and the second side margin portion 115 can be 100 μm or less, preferably 30 μm or less, and for ultra-small products, more preferably 20 μm or less.
[0107] Here, the width wm of the side margin portions 114, 115 may refer to the size in the third direction of each of the side margin portions 114, 115. In addition, the width wm of the side margin portions 114, 115 may refer to the average width wm of the side margin portions 114, 115, or may refer to the average size in the third direction of the side margin portions 114, 115.
[0108] The average size in the third direction of the side margin portions 114, 115 may be measured by scanning an image of a cross-section in the first and third directions of the body 110 with a scanning electron microscope (SEM) at a magnification of 10,000. More specifically, it may mean an average value calculated by measuring the size in the third direction at 10 points equally spaced in the first direction in an image obtained by scanning one side margin portion.
[0109] In one embodiment of the present invention, a structure in which the ceramic electronic component 100 has two external electrodes 131, 132 is described, but the number and shapes of the external electrodes 131, 132 can be changed depending on the shape of the internal electrodes 121, 122 and other purposes.
[0110] The outer electrodes 131 and 132 may be disposed on the body 110 and connected to the inner electrodes 121 and 122 .
[0111] More specifically, the external electrodes 131, 132 may include a first external electrode 131 and a second external electrode 132 disposed on the third surface 3 and the fourth surface 4 of the body 110, respectively, and connected to the first internal electrode 121 and the second internal electrode 122, respectively. That is, the first external electrode 131 may be disposed on the third surface 3 of the body and connected to the first internal electrode 121, and the second external electrode 132 may be disposed on the fourth surface 4 of the body and connected to the second internal electrode 122.
[0112] The external electrodes 131, 132 may be formed using any material that has electrical conductivity, such as a metal, and the specific material may be determined taking into consideration electrical characteristics, structural stability, etc., and may further have a multi-layer structure.
[0113] For example, the external electrodes 131, 132 may include electrode layers 131a, 132a disposed on the body 110 and plating layers 131b, 132b disposed on the electrode layers 131a, 132a.
[0114] As a more specific example of the electrode layers 131a and 132a, the electrode layers 131a and 132a may be fired electrodes containing a conductive metal and glass, or resin-based electrodes containing a conductive metal and resin.
[0115] Also, the electrode layers 131a and 132a may be in a form in which a fired electrode and a resin-based electrode are sequentially formed on the body 110.
[0116] In addition, the electrode layers 131a and 132a may be formed by transferring a sheet containing a conductive metal onto the body 110, or may be formed by transferring a sheet containing a conductive metal onto a fired electrode.
[0117] The conductive metal used for the electrode layers 131a and 132a is not particularly limited as long as it can be electrically connected to the internal electrodes 121 and 122 to form capacitance, and may include, for example, at least one selected from the group consisting of nickel (Ni), copper (Cu), palladium (Pd), silver (Ag), gold (Au), platinum (Pt), tin (Sn), tungsten (W), titanium (Ti), and alloys thereof. The electrode layers 131a and 132a may be formed by applying a conductive paste prepared by adding glass frit to the conductive metal powder, and then firing the paste.
[0118] The plating layers 131b and 132b can serve to improve mounting characteristics.
[0119] The type of plating layers 131b, 132b is not particularly limited, and may be a single layer plating layer 131b, 132b containing one or more of nickel (Ni), tin (Sn), palladium (Pd), and alloys thereof, or may be formed of multiple layers.
[0120] As a more specific example of the plating layers 131b, 132b, the plating layers 131b, 132b may be Ni plating layers or Sn plating layers, and may be in a form in which a Ni plating layer and a Sn plating layer are sequentially formed on the electrode layers 131a, 132a, or in a form in which a Sn plating layer, a Ni plating layer, and a Sn plating layer are sequentially formed. The plating layers 131b, 132b may also include a plurality of Ni plating layers and / or a plurality of Sn plating layers.
[0121] The size of the multilayer electronic component 100 does not need to be particularly limited.
[0122] However, in order to simultaneously achieve miniaturization and high capacity, the thickness of the dielectric layers and internal electrodes must be reduced and the number of layers must be increased, so the effects of the present invention are more pronounced in a multilayer electronic component 100 having a size of 3216 (length x width: 3.2 mm x 1.6 mm) or less, preferably 1005 (length x width: 1.0 mm x 0.5 mm) or less.
[0123] The present invention will be described in more detail below with reference to examples. However, these examples are intended to aid in the specific understanding of the invention, and the scope of the present invention is not limited to these examples.
[0124] (Example) The main component base material was a mixture of cube-shaped BaTiO3 particles with an average particle size of 100 nm that formed the core part and spherical BaTiO3 particles with an average particle size of 10 nm that formed the shell part, which were mixed according to the design ratio. Zirconia beads were used as a mixing / dispersion medium, and additive particles such as dysprosium (Dy), ethanol / toluene solvent, cube and spherical BaTiO3, and dispersant were mixed together and milled for 5 hours, and then a binder was mixed and milled for another 5 hours. The slurry produced in this way was used in a sheet production molding machine to produce molded sheets with thicknesses of 0.8 μm and 0.6 μm. Nickel (Ni) internal electrodes were printed on the molded sheets. The upper and lower cover parts were manufactured by laminating 25 layers of cover sheets with an average thickness of 10μm to 13μm, and 31 layers of sheets printed with nickel (Ni) internal electrodes were pressed and laminated to manufacture bars. The compressed bars were cut into chips of 3216 (length x width: 3.2mm x 1.6mm) size using a cutting machine. The completed 3216 size MLCC chips were calcined and then fired in a reducing atmosphere of 0.1% H2 / 99.9% N2~0.5% H2 / 99.5% N2 (H2O / H2 / N2 atmosphere) at 1100~1150℃ for 10 minutes, and then reoxidized in a N2 atmosphere at 1000℃ for 0.5 hours. Here, 0.1% hydrogen concentration corresponds to an electromotive force of 670mV in an environment measured at 850℃ using an oxygen partial pressure meter, and 0.5% hydrogen concentration corresponds to an electromotive force of 760mV. The fired chip was subjected to a termination process using copper paste and the electrodes were fired to complete the external electrodes. As a result, a 3216 size MLCC chip was manufactured with a dielectric layer (meaning the dielectric layer placed between internal electrodes) thickness of approximately 0.4μm after firing, and 30 dielectric layers.
[0125] The room temperature capacitance and dielectric loss of the MLCC chip were measured using an LCR meter at 1 kHz and AC 0.5 V / μm. The dielectric constant of the MLCC chip dielectric was calculated from the capacitance, dielectric thickness, internal electrode area, and number of layers of the MLCC chip. The room temperature insulation resistance was measured after 60 seconds of applying DC 10 V / μm to 10 samples taken at 10 pieces each. The change in capacitance due to temperature was measured in the temperature range of -55°C to 105°C. For the accelerated life test (HALT: Highly Accelerated Life Time Test), a voltage corresponding to an electric field of 23 V / μm was applied at 125°C to 40 samples for each test example (comparative example and example), and the time until failure occurred was measured and the mean time to failure (MTTF: Mean Time to Failure) was calculated. In addition, the DC bias change rate of the capacitance was measured while applying DC voltages of 1 V and 3 V to the chip.
[0126] The comparative example used conventional circular dielectric particles, and it was confirmed that the shape of the core portion after sintering based on the TEM-EDS observation results was substantially circular and did not contain any core portions with different polygonal shapes.
[0127] In the embodiment, the hexahedral dielectric particles of the present invention were used, and it was confirmed that after firing, a plurality of core parts included different polygonal shapes from each other in the TEM-EDS observation results. The manufacturing conditions were the same as those of the comparative example.
[0128] The DC-Bias change rate refers to the rate of change in dielectric capacitance when DC voltages of 1 V and 3 V are applied, based on the dielectric capacitance when no DC voltage is applied.
[0129] The severe reliability evaluation (HALT, Highly Accelerated Life Test) was performed by measuring the mean time to failure (MTTF) when a voltage of 1.5Vr was applied at a temperature of 125°C. Initial insulation resistance (R0) 10 9When a short circuit occurred based on Ω, it was determined that a failure had occurred. In both the comparative example and the example, 400 sample chips were used, and the average time until all the sample chips failed was calculated as the MTTF.
[0130] [Table 1]
[0131] As can be seen from Table 1, in the case of the comparative example, the dielectric constant is 3230, the DC-Bias change rate shows a capacitance change rate of -27% when 1V is applied with respect to no voltage application, and a capacitance change rate of -77% when 3V is applied, and the MTTF was measured at 32.5 hours during the HALT evaluation. On the other hand, in the case of the embodiment, the dielectric constant is improved to 3810 compared to the comparative example, and the DC-Bias change rate shows a capacitance change rate of -18% when 1V is applied with respect to no voltage application, and a capacitance change rate of -68% when 3V is applied, so it can be confirmed that the capacitance change rate is also improved compared to the comparative example. In addition, the MTTF was measured at 54.9 hours during the HALT evaluation, and it can be seen that the mean time to failure was improved compared to the comparative example. This shows that the dielectric constant and DC-Bias characteristics of the laminated electronic component including the dielectric crystal grains having a polygonal core portion are improved compared to the laminated electronic component including the dielectric crystal grains having a circular core portion.
[0132] Although the embodiments of the present invention have been described in detail above, the present invention is not limited to the above-described embodiments and the accompanying drawings, but is limited by the scope of the accompanying claims. Therefore, various substitutions, modifications, and changes can be made by a person having ordinary knowledge in the art within the scope of the technical idea of the present invention described in the claims, and these also belong to the scope of the present invention.
[0133] In addition, the expression "one embodiment" used in this specification does not mean the same embodiment, but is provided to emphasize and describe each unique feature that is different from the others. However, the above-mentioned one embodiment does not exclude being realized in combination with the features of another embodiment. For example, even if a matter described in a specific embodiment is not described in another embodiment, it can be understood as a description related to the other embodiment, unless there is a description in the other embodiment that is opposite or contradictory to the matter.
[0134] The terms used in this specification are merely used to describe one embodiment and are not intended to limit the present disclosure. In this case, the singular expression includes the plural expression unless the context clearly indicates otherwise. [Explanation of symbols]
[0135] 100 Multilayer electronic components 110 Main unit 111 Dielectric layer 112, 113 Cover part 114, 115 Side margin 121, 122 Internal electrode 131, 132 External electrode 10 Dielectric grains 10' Dielectric particles 11, 11' Core section 12, 12' Shell
Claims
1. a body including a dielectric layer and an internal electrode; an external electrode disposed on the body; the dielectric layer includes a plurality of dielectric crystal grains; At least one of the plurality of dielectric crystal grains has a core-shell structure including a core portion and a shell portion surrounding at least a portion of the core portion, The cross section of the core portion includes a polygon, the average length of the plurality of dielectric crystal grains is 80 nm or more and 200 nm or less; A multilayer electronic component, wherein the length of the core portion is 70% or more of the length of the dielectric crystal grains.
2. 2. The multilayer electronic component according to claim 1, wherein the dielectric crystal grains of the core-shell structure include core portions having cross sections of mutually different polygonal shapes.
3. 2. The multilayer electronic component according to claim 1, wherein the polygons include one or more of: triangles including equilateral triangles and isosceles triangles; quadrilaterals including squares, rectangles, rhombus, trapezoids, equilateral trapezoids, and parallelograms; pentagons; and hexagons.
4. 2. The multilayer electronic component according to claim 1, wherein a sum of interior angles of the polygon is substantially one or more of 180°, 360°, 540°, and 720°.
5. 5. The multilayer electronic component according to claim 4, wherein the interior angle is an angle between straight lines extending from different sides.
6. a dielectric grain boundary is disposed between the plurality of dielectric grains; 2. The multilayer electronic component according to claim 1, wherein at least a part of a cross-sectional shape of said core portion is substantially parallel to a dielectric crystal grain boundary.
7. The multilayer electronic component according to claim 1 , wherein the shell portion contains a rare earth element.
8. 2. The multilayer electronic component according to claim 1, wherein the dielectric layer includes a plurality of dielectric layers, and at least one of the plurality of dielectric layers has an average thickness of 0.45 μm or less.
9. 2. The multilayer electronic component according to claim 1, wherein the internal electrodes include a plurality of internal electrodes, at least one of the plurality of internal electrodes having an average thickness of 0.45 [mu]m or less.
10. the body includes a capacitance forming portion including the dielectric layers and the internal electrodes arranged alternately with the dielectric layers in a first direction, and cover portions respectively arranged on both end surfaces of the capacitance forming portion in the first direction, the body including a first surface and a second surface facing each other in the first direction, a third surface and a fourth surface connected to the first surface and the second surface and facing each other in the second direction, and a fifth surface and a sixth surface connected from the first surface to the fourth surface and facing each other in the third direction, The multilayer electronic component according to claim 1 , further comprising side margin portions disposed on the fifth surface and the sixth surface of the main body, respectively.
11. The multilayer electronic component according to claim 1 , wherein the multilayer electronic component has a size of 1005 (length×width: 1.0 mm×0.5 mm) or less.
12. The multilayer electronic component according to claim 1 , wherein the external electrodes include an electrode layer disposed on the body and connected to the internal electrodes, and a plating layer disposed on the electrode layer.
13. a body including a dielectric layer and an internal electrode; an external electrode disposed on the body; the dielectric layer includes a plurality of dielectric crystal grains; At least one of the plurality of dielectric crystal grains has a core-shell structure including a core portion and a shell portion surrounding at least a portion of the core portion, The core portion includes a hexahedral shape, the average length of the plurality of dielectric crystal grains is 80 nm or more and 200 nm or less; A multilayer electronic component, wherein a volume of the core portion is 30% or more of a volume of the dielectric crystal grains.
Citation Information
Patent Citations
Multilayered Capacitor and Manufacturing Method the Same
KR1020170127647A
Dielectric composition and multilayer ceramic capacitor having the same
KR1020180073359A